(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The objective of this article is to analyses new concepts for leadership and management and create a new impression known as the Mirror Leadership. If a company has to develop new eaders, it gives employee managers an image of their leadership elegance. Management and leadership differ significantly. The first addresses doubts and the latter addresses change and the management and administration of all groups together. Any strategy of action requires defining what will be achieved, creating interpersonal relationships with those that may help to achieve a common goal, and lettering an item to ensure that particular personnel undertake their work. Each personthese three behaviors differently. Most businesses must strengthen their leadership skills. Successful organizations should not wait until leaders appear. Successful firms look to young leaders and put them in areas that they don’t know about to support them. With careful study, education and incentive more individuals are leading within organizations.